Pengaruh Lama Penyimpanan terhadap Kerusakan Asam Lemak Omega-3 pada Air Susu Ibu (ASI) - Aryani, Titin; Utami, Fitria Siswi; Sulistyaningsih, Sulistyaningsih; Ulfah Muawanah, Isnin Aulia (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2016)
Background: This quantitative research aimed to determine the effect of storage time to damage omega-3 fatty acids in breast milk (ASI). Method: Data were analyzed using GC-MS (Gas Chromatography-Mass Spectrometry) chromatograms of data. Results: The data generated was breast milk (ASI) stored in the freezer temperature (00C) for 0, 7 and 30 days had a percent relative contents of omega-3, respectively for 29.12, 28.24 and 6.24. Based on the Kruskal Wallis Test, obtained p value=0.018 (p<0.05). Conclusion: This statistical result showed that there was the effect of storage time to damage omega-3 fatty acids in breast milk.